Enkripsi Base 64, Hashing SHA1 dan MD5 pada QR Code Presensi Kuliah - Witriyono, Harry; Fernandez, Sandhy (JSAI (Journal Scientific and Applied Informatics), 2021)
The lecture attendance application at the University of Muhammadiyah Bengkulu needs to be developed so that it is easier in the implementation process. One way to simplify the process is to use the presence of a Quick Response Code which can be done in online or offline lectures. The method used is in the form of encrypted and hashed Uniform Resource Locator storage combined with internet protocol address filtering so that the information stored in the Quick Response Code becomes more secure than in plain text. The data collection method uses observation and interview techniques to previous application users and then analysis, design and experimental programming are carried out on program modules that play a role in the presence process. From the results of this study, the Quick Response Code can be protected and used successfully and can be integrated with several learning management systems, social media applications that are often used by lecturers, especially at the University of Muhammadiyah Bengkulu. The results of this study have been used in the lecture process in the Even Semester of the 2020 Academic Year.